SHIPWORMS (MOLLUSCA: BIVALVIA: TEREDINIDAE) FROM A BRAZILIAN NORTHEAST ESTUARY - Vidal, Juliana Maria Aderaldo; Barreira, Cristina de Almeida Rocha (Arquivos de Ciências do Mar, 2009)
Teredinids are the most representative group of the marine wood-boring organisms, and for the fi rst time boring mollusks from this family are being studied in Ceará State, Brazil. This work was aimed to record and characterize the communities settled in the mangrove forest along the Jaguaribe River estuary, considering their morphological features. Seven sampling stations were established along the right bank of the estuary, at a distance of 18 km from the Aracati Bridge at the river mouth. Six species were identifi ed, namely Neoteredo reynei, Lyrodus massa, Teredo turnerae, Nausitora fusticula, Bankia cf. bagidaensis, and Bankia cf. fi mbriatula, which were described and their geographic distribution recorded. All the found species are the fi rst reported occurrence for the littoral of Ceará State. However, this is due to the lack of investigations on this group in the State although the occurrence of those animals in this region was expected. The specimens were incorporated into the “Prof. Henry Ramos Matthews Malacological Collection” of Instituto de Ciências do Mar, Federal University of Ceará.